Energy Potential Generated from Municipal Solid Waste (MSW) at Tamangapa Landfill in Makassar City - Andi Zulfikar Syaiful; M. Tang; Hermawati Hermawati; Djusdil Akrim; Annisa Sila Puspita (Postgraduate, University of Mataram, 2024)
This study aims to analyse the potential energy that can be generated from municipal solid waste (MSW) at Tamangapa landfill, check the adequacy of energy according to the target of 20 MW/day, and give consideration to WtE technologies that can be applied. The research began with a literature study, followed by a quantitative approach to calculate the potential energy that can be generated through incineration, gasification, pyrolysis, anaerobic digestion (AD) and fermentation WtE technologies. The results showed that the energy target of 20 MW/day from MSW in Makassar can be met through incineration (168.80 MW/day), gasification (28.29 MW/day) and pyrolysis (62.03 MW/day). However, if 20 MW/day is clean energy, then considering the energy conversion efficiency, 30.38 MW/day is obtained for incineration, 7.07 MW/day for gasification, and 15.51 MW/day for pyrolysis. Based on this calculation, only incineration technology can fulfil the 20 MW/day energy target as expected. In order to maximise the energy potential, it is recommended to use a combination of incineration WTE technologies for plastic, rubber, paper and fabric components, and pyrolysis for wood and food waste components.